(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
The development of students’ communicative competence in English language lessons is one of the central objectives of modern philological education. Communicative competence includes not only grammatical knowledge, but also the ability to use language appropriately, fluently, and effectively in real social, academic, and professional contexts. In higher education institutions, especially in philological universities, English language teaching should be directed toward forming students’ linguistic, sociolinguistic, discourse, strategic, and intercultural skills. This article examines pedagogical approaches to developing communicative competence through interactive tasks, dialogic learning, problem-based activities, role-play, project work, authentic materials, and digital resources. Special attention is paid to the conditions of English language education in Uzbekistan, where the need for professionally competent, culturally aware, and communicatively active specialists is increasing. The study emphasizes that effective development of communicative competence requires a learner-centered methodology, systematic practice, integration of language skills, and continuous assessment of students’ communicative progress.